Evaluating the Cytotoxicity of Functionalized MWCNT and Microbial Biofilm Formation on PHBV Composites - Montanheiro, Thaís Larissa do Amaral; Schatkoski, Vanessa Modelski; Camarena, Denisse Esther Mallaupoma; de Oliveira, Thais Cardoso; da Silva, Diego Morais [UNESP]; Vegian, Mariana Raquel da Cruz [UNESP]; Catalani, Luiz Henrique; Koga-Ito, Cristiane Yumi [UNESP]; Thim, Gilmar Patrocínio (MDPI, 2024)
This study focuses on the cytotoxic evaluation of functionalized multi-walled carbon nanotubes (MWCNT) and microbial biofilm formation on poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) nanocomposites incorporating MWCNTs functionalized with gamma-aminobutyric acid (GABA) and carboxyl groups. The materials were characterized for cytotoxicity to fibroblasts and antimicrobial effects against Escherichia coli, Staphylococcus aureus and Candida albicans. The functionalization of MWCNTs was performed through oxidation (CNT-Ox) and GABA attachment (CNT-GB). The PHBV/CNT nanocomposites were produced via melt mixing. All MWCNT suspensions showed non-toxic behaviors after 24 h of incubation (viability higher than 70%); however, prolonged incubation and higher concentrations led to increased cytotoxicity. The antibacterial potential of PHBV/CNT nanocomposites against S. aureus showed a reduction in biofilm formation of 64% for PHBV/CNT-GB and 20% for PHBV/CNT-Ox, compared to neat PHBV. Against C. albicans, no reduction was observed. The results indicate promising applications for PHBV/CNT nanocomposites in managing bacterial infections, with GABA-functionalized CNTs showing enhanced performance.
Keywords: biofilm formation; carbon nanotube; cytotoxicity; nanocomposite; poly(3-hydroxybutyrate-co-3-hydroxyvalerate)